2014
DOI: 10.4236/oju.2014.43005
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors of Extracorporeal Shock Wave Lithotripsy (ESWL) for Renal & Ureteric Calculi in Adult

Abstract: The purpose of this study was to define factors that have a significant impact on the stone-free rate after ESWL. Methods: A total of 417 patients harboring renal or ureteral stones underwent extracorporeal shock wave lithotripsy (ESWL) between October 2008 and July 2012. Eighty five patients were lost on follow up. The remaining (n = 332). All patients were >18 yr of age. Siemens and SLX-F2 electromagnetic machines were used to impart shock waves. Patients were stratified according to localization (pelvic, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Also, no correlation was found between ESWL success rates and stone opacity in two other studies. [13,20] Operation time was not different between the two groups in univariate analysis in our study. Falahatkar et al [21] also did not report any relationship between surgery time and stone opacity in complete supine PCNL procedures.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Also, no correlation was found between ESWL success rates and stone opacity in two other studies. [13,20] Operation time was not different between the two groups in univariate analysis in our study. Falahatkar et al [21] also did not report any relationship between surgery time and stone opacity in complete supine PCNL procedures.…”
Section: Discussionmentioning
confidence: 51%
“…[8] So far, some studies have investigated stone opacity effect on ESWL outcomes. [12,13] Also, some other studies have studied the relationship between stone density and ESWL or PCNL outcomes. [14][15][16][17] To our knowledge, no study has compared the results of PCNL in patients with radiopaque and radiolucent stones.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of treatment after ESWL is variable due to the close relation between the final result with the different concepts of success. 5 Many studies have demonstrated that the consistency, size, shape, location, and density of ureteral stones and body mass index (BMI) may be predictors of the outcome of ESWL. 6 Therefore it is very important to estimate the probability of stone clearance for each individual so as to determine who will experience maximum benefit from ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…4 It is not certain which factors influence the outcome of ESWL. 5 Therefore the present study was planned to determine the most significant factors that influence on the success of ESWL of ureteric calculi in Asian Indian patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although it can cause some acute effects in the kidney, there is no long-term effect on the growing kidneys of children. [8] concluded that ESWL remained one of the most commonly utilized treatments for patients with upper urinary tract calculi; stone diameter, location, and number of shock waves were the most important predictors determining stone clearance after ESWL of renal and ureteric calculi. It was found that age and sex had no effect on ESWL success rate also in other studies these factors found play no effect.…”
Section: Introductionmentioning
confidence: 99%